The compelling link between physical activity and the body's defense system - David C. Nieman; Laurel M. Wentz (Elsevier, 2019)
This review summarizes research discoveries within 4 areas of exercise immunology that have received the most attention from investigators: (1) acute and chronic effects of exercise on the immune system, (2) clinical benefits of the exercise-immune relationship, (3) nutritional influences on the immune response to exercise, and (4) the effect of exercise on immunosenescence. These scientific discoveries can be organized into distinctive time periods: 1900-1979, which focused on exercise-induced changes in basic immune cell counts and function; 1980-1989, during which seminal papers were published with evidence that heavy exertion was associated with transient immune dysfunction, elevated inflammatory biomarkers, and increased risk of upper respiratory tract infections; 1990-2009, when additional focus areas were added to the field of exercise immunology including the interactive effect of nutrition, effects on the aging immune system, and inflammatory cytokines; and 2010 to the present, when technological advances in mass spectrometry allowed system biology approaches (i.e., metabolomics, proteomics, lipidomics, and microbiome characterization) to be applied to exercise immunology studies. The future of exercise immunology will take advantage of these technologies to provide new insights on the interactions between exercise, nutrition, and immune function, with application down to the personalized level. Additionally, these methodologies will improve mechanistic understanding of how exercise-induced immune perturbations reduce the risk of common chronic diseases. Keywords: Aging, Exercise, Immunology, Infection, Inflammation, Mass Spectrometry, Nutrition